Cellular Infiltrate in Rheumatoid Arthritis Associated Paracentral Corneal Ulceration - Kalsow, Carolyn M. (Ocul Immunol Inflamm, 2016)
PURPOSE. To investigate an immunopathogenesis of central and paracentral corneal ulceration associated with rheumatoid arthritis. METHODS. Sparse infiltrating cells in the ulcer area were identified by immunohistochemistry applied to archived formalin fixed, paraffin embedded tissues that had been recovered from patients undergoing penetrating keratoplasty necessitated by rheumatoid associated central or paracentral corneal ulceration. RESULTS: Clinically the ulcers presented as noninfiltrated lesions with a modicum of other ocular inflammation. Sparse T lymphocytes were consistently identified in the subepithelial areas adjacent to the ulcer, with some neutrophils and macrophages in the stroma. B lymphocytes were not detected. MHC Class II antigens reactivity was noted on some infiltrating cells and on corneal endothelium of 2 specimens. CONCLUSION: Immunohistochemistry of archival tissue facilitated detection and identification of sparse infiltrate into this infrequent corneal melting. Selective, consistent finding of T lymphocyte infiltration in the ulcer area supports an immunopathogenesis of this clinical entity.